Role of Anti-Müllerian Hormone in the Pathogenesis of Polycystic Ovary Syndrome - Dewailly, Didier; Barbotin, Anne-Laure; Dumont, Agathe; Catteau-Jonard, Sophie; Robin, Geoffroy (Frontiers in Endocrinology, 2020)
Besides its interest for diagnosis, the finding of an elevated serum AMH level in PCOS has open major pathophysiological issues. This review addresses the three most important issues: 1- the role of AMH in the disturbed folliculogenesis of PCOS; 2- the role of AMH in the gonadotropin dysregulation of PCOS and 3- the role of AMH in the trans-generational transmission of PCOS. For each of those issues, the clinical and experimental evidences currently available are discussed and physiopathological hypothesis are proposed.